Analisis SWOT dalam Penentuan Strategi Keamanan Siber pada Implementasi Sistem Internet of Defense Things (IoDT) 5.0 di Industri Pertahanan (PT. Dirgantara Indonesia, PT. Len Industri, dan PT. Pindad) - Ra’idah Naufaliana Dewi; H.A Danang Rimbawa; Bisyron Wahyudi (Journal on Education, 2025)
This study examines the implementation of the Internet of Defense Things (IoDT) 5.0 within the Indonesian defense industry, focusing on cybersecurity aspects. Through a SWOT analysis, the research identifies internal and external factors influencing the success or challenges of IoDT 5.0 implementation. Data collected via observations and questionnaires at PT. Pindad, PT. Dirgantara Indonesia, and PT. Len Industri in Bandung reveal key insights into the effectiveness of access management processes, incident response in cybersecurity, organizational culture and employee awareness of cybersecurity, the readiness of cybersecurity infrastructure, and the competencies of cybersecurity human resources. The findings highlight the critical need to strengthen access management procedures, enhance employee awareness, improve cybersecurity infrastructure, and develop the skills of cybersecurity professionals to address escalating threats. This research provides valuable insights into the challenges and strategic approaches for advancing IoT 5.0 in Indonesia's defense sector.